Effects of bonus issues. - Husin Tjandra. (2009)
Extensive research has been done with regard to the effect and benefits of bonus share issues. There are different views regarding the effects of bonus share issues : • Fundamentalists argue that bonus share issues will not benefit investors because the equity of the company remains the same. Thus, investors will get "nothing" out of "nothing". • Others believe that they can reap abnormal profits from bonus share issues as a bonus share issue is an indication (signal) of better future for the company.